2019
DOI: 10.1021/acsnano.9b08037
|View full text |Cite
|
Sign up to set email alerts
|

Probing Multiphased Transition in Bulk MoS2 by Direct Electron Injection

Abstract: Structural phase transitions in layered two-dimensional (2D) materials are of significant interest owing to their ability to exist in multiple metastable states with distinctive properties. However, phase transition in bulk MoS2 by nondestructive electron infusion has not yet been realized. In this study, we report the 2H to 1T′ phase transition and in-between intermediates in bulk MoS2 using MoS2/[Ca2N]+·e– heterostructures, in which kinetic free electrons were directly injected into MoS2. We observed various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 62 publications
2
47
0
Order By: Relevance
“…As the treatment time increased, the softening and broadening of the Raman modes increased, indicating an increase in the electron density and electron−phonon coupling. 8,12,32,33 We note that each Raman frequency displayed slightly different amounts of red-shift because of the different origins of the vibrational modes. 12,32,33 The inplane mode at 212.8 cm −1 showed red-shifts of 1, 1.6, and 3.1 cm −1 with 3, 6, and 9 h Li treatment, respectively, as indicated by the dashed line in Figure 4a (see Table S2 for details on the softening of other modes).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As the treatment time increased, the softening and broadening of the Raman modes increased, indicating an increase in the electron density and electron−phonon coupling. 8,12,32,33 We note that each Raman frequency displayed slightly different amounts of red-shift because of the different origins of the vibrational modes. 12,32,33 The inplane mode at 212.8 cm −1 showed red-shifts of 1, 1.6, and 3.1 cm −1 with 3, 6, and 9 h Li treatment, respectively, as indicated by the dashed line in Figure 4a (see Table S2 for details on the softening of other modes).…”
Section: Resultsmentioning
confidence: 92%
“…8,12,32,33 We note that each Raman frequency displayed slightly different amounts of red-shift because of the different origins of the vibrational modes. 12,32,33 The inplane mode at 212.8 cm −1 showed red-shifts of 1, 1.6, and 3.1 cm −1 with 3, 6, and 9 h Li treatment, respectively, as indicated by the dashed line in Figure 4a (see Table S2 for details on the softening of other modes). By increasing the treatment time to 12 h, the Raman modes were distinctively quenched, which is attributed to the Pauli blocking induced by the high electron density.…”
Section: Resultsmentioning
confidence: 92%
“…6 c that illustrates the band profiles and band alignment between the undoped MoS 2 and BV doped MoS 2 regions. The work function of the pristine MoS 2 has been reported to be in the range of 4.6–4.9 eV 61 64 . Although, the exact work function of BV doped MoS 2 is not known, we expect this to be lower than MoS 2 due to the increased carrier concentration by doping as the work function is known to be modulated by p or n-doping 5 , 65 .…”
Section: Resultsmentioning
confidence: 99%
“… 13 The electron anion between the positively charged Y 2 C layers possesses more electrons than that in Ca 2 N. Kim et al combined 2D electrides with the layered material MoTe 2 . 14 The 2D electride [Ca 2 N] + ·e – diffuses electrons into MoTe 2 , producing an electron doping density in excess of 1.6 × 10 14 cm –2 and introducing changes in the lattice symmetry. Dhakal et al reported the 2H to 1T′ phase transition and intermediates in bulk MoS 2 by using MoS 2 /[Ca 2 N] + ·e – heterostructures.…”
Section: Introductionmentioning
confidence: 99%